2012
DOI: 10.1007/s13139-012-0169-1
|View full text |Cite
|
Sign up to set email alerts
|

Peripheral Tuberculous Lymphadenitis Masquerading as Metastatic Gastric Carcinoma on F-18 FDG Dual Time Point PET/CT

Abstract: A 59-year-old woman was hospitalized with weight loss, anorexia, and low grade fever for 2 weeks. She had undergone a total gastrectomy followed by adjuvant chemotherapy 10 years prior due to advanced gastric cancer. To evaluate recurrence, fluorine-18 fluorodeoxyglucose (FDG) dual time point positron emission tomography/computed tomography (DTPP) was conducted with a Gemini GXL 6 PET/CT system (Philips, Hamburg, Germany). FDG DTPP was performed twice, with an early scan 60 min after FDG injection and a delaye… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

0
2
0
2

Year Published

2013
2013
2021
2021

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(4 citation statements)
references
References 8 publications
0
2
0
2
Order By: Relevance
“…The common histopathologic findings were cortical follicular hyperplasia with anthracotic pigmentation and macrophage infiltration. Microscopic fibrotic nodules could also be found in the medulla [37,38]. A similar study also showed that calcification or high attenuation at LNs on CT, even with 18 F-FDG activity, indicated they were benign in a tuberculosis endemic region [39].…”
Section: Discussionmentioning
confidence: 68%
“…The common histopathologic findings were cortical follicular hyperplasia with anthracotic pigmentation and macrophage infiltration. Microscopic fibrotic nodules could also be found in the medulla [37,38]. A similar study also showed that calcification or high attenuation at LNs on CT, even with 18 F-FDG activity, indicated they were benign in a tuberculosis endemic region [39].…”
Section: Discussionmentioning
confidence: 68%
“…The ΔSUVmax were also significantly higher for malignant lesions than for benign ones [54]. On the other hand, it had been reported that some inflammatory, granulomatous and active infectious diseases may show higher 18 F-FDG uptake on delayed PET imaging, similar to malignant lesions, possibly due to 18 F-FDG -avidity of activated inflammatory cells involved [55].…”
Section: Discussionmentioning
confidence: 99%
“…Peu d'é tudes ont exploré l'inté rêt du DTP dans le bilan des né oplasies gastriques [90][91][92]. Dans une sé rie de 74 patients, Cui et al ont ré alisé une seconde acquisition d'images 120 min aprè s l'injection du 18 F-FDG lorsqu'un hypermé tabolisme focal é tait observé au niveau de la paroi gastrique aprè s 60 min et ont ainsi montré que la SUVmax tardive, mais plus encore la diffé rence de SUV entre les deux temps d'examen, permettaient de distinguer une pathologie bé nigne d'une maligne [92].…”
Section: Cancers Digestifsunclassified
“…Sun et al ont reporté l'inté rêt d'une acquisition DTP 18 F-FDG TEP chez un patient de 73 ans avec douleurs abdominales supé rieures et augmentation majeure du taux sé rique d'alphafoetoproté ine pour faire le diagnostic d'adé nocarcinome hé patoïde de l'estomac [91]. Kim et al ont illustré les limites de la technique avec un patient aux anté cé dents de né oplasie gastrique pré sentant de multiples adé nopathies sus-et sous-diaphragmatiques chez qui une acquisition DTP a é té ré alisé e et qui montrait une majoration de la SUV pour toutes les lé sions entre les deux temps d'acquisition, alors que le diagnostic final é tait une tuberculose [90]. Enfin, dans une sé rie de 50 patients avec un hypermé tabolisme focal duodé nal (32 malins, 18 bé nins), Sa et al ont montré que les SUVmax pré coce (60 min) et tardive (120 min) pré sentaient des performances similaires pour distinguer les lé sions malignes, alors que la diffé rence de SUV entre les deux temps d'examen donnait des ré sultats bien plus modestes [93].…”
Section: Cancers Digestifsunclassified